Isolation and whole genome sequencing of fetal cells from maternal blood towards the ultimate non‐invasive prenatal testing. (29th December 2017) - Chen, Fang; Liu, Ping; Gu, Ying; Zhu, Zhu; Nanisetti, Amulya; Lan, Zhangzhang; Huang, Zhiwei; Liu, Jia Sophie; Kang, Xiongbin; Deng, Yuqing; Luo, Liqiong; Jiang, Dan; et al.
Abstract: Objective: The purpose of this study were to develop a methodology of isolating fetal cells from maternal blood and use deep sequence demonstrating the promise for complete and accurate genetic screening compared to other non‐invasive prenatal testing. Methods: Here in this study, we developed a double negative selection (DNS) procedure to unbiasedly enrich fetal cells. After validated by short tandem repeat (STR), the isolated circulating fetal cells (CFCs) were subjected to deep whole genome sequencing analysis. Results: Our DNS protocol significantly increasing the purity of the mimic fetal cells from 1 in 1 million nucleated cells in whole blood to 1:8 to 1:30 (12.5%‐3.33%) after 2 steps of enrichment. Isolated single fetal cell obtained a coverage rate (86.8%) and allelic dropout rate (24.90%) comparative to the reported results of human cell line. Several disease‐associated variants were identified in the whole genome sequencing data of isolated CFCs and further confirmed in the sequencing data of unamplified gDNA. Conclusion: In conclusion, the robustness of DNS and STR to collect CFCs from peripheral maternal blood for the first time coupled with deep sequencing technique demonstrates the possibility of comprehensive non‐invasive prenatal testing of genetic disorders using isolated CFCs. Abstract : What's already known about this topic? Fetal cells retrieved from the maternal circulation hold great potential to provide whole genome information for prenatal screening and diagnosis. However, none of the reported methods have successfully shown circulating fetal cells (CFCs) isolation combined with deep sequencing. What does this study add? For the first time, we successfully isolated CFCs followed by whole genome sequencing (WGS) at high coverage, demonstrating the possibility of comprehensive non‐invasive prenatal testing of genetic disorders.